Modelo de productividad de David Sumanth aplicado a una empresa del sector de maquinaria no eléctrica - Jiménez Rojas, Álvaro Hernán; Delgado, Edwin Eduardo; Gaona Villate, Germán (Ingeniería, 2000)
The Colombian sectors and manufacturer companies are facing the challenge at the present time about the design, the implementation and the control of the strategies which allows to improve their competitiveness, with the objective of the benchmark not only with national companies but also with foreigner ones. The productivity is focusing to be a strategic tool for the achievement and improvement of the competitiveness, it is based on the main objective to give to the manufacturer companies the application of an integ rated model with the following cicle: Measurement, Evaluation, Planning and Improvement, all of them based on the Operative Model of Total Productivity of David Sumanth;which was implemented in a company of the sector of non electric machinery but its methodology and results can be applied to any company of our industry. Key words: Productivity, Measurement,Evaluation, Planning, and Improvement.